1982
DOI: 10.1037/0022-006x.50.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus variables in the block design task.

Abstract: Block-design construction tasks reliably assess cognitive deficits due to brain injury. We examined the important aspects of this task with four experiments using normal subjects. Two problem-solving strategies are identified: an analytic strategy in which subjects mentally segment each block in the design to be constructed and a synthetic strategy, which involves wholistic pattern matching. Three experiments found a predominate analytic strategy. The time to place a single test block in a display decreased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 8 publications
1
41
0
Order By: Relevance
“…Among these, the "block-selection" operation pertains to the time required for selecting a surface from the alternatives presented by the block faces so that it matches a given mentally recoded stimulus unit (a perceived portion of the stimulus pattern that has been reprocessed into units like those of the various block faces). Experimental manipulations of relevant task parameters have shown that when attempting to find such a match, subjects take longer to select a correctly oriented two-color surface than a correctly oriented solid-color surface (Royer, 1977;Schorr, Bower, & Kiernan, 1982).…”
Section: Daniel B Berch and Mark M Leach University Of Cincinnat~ Cmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these, the "block-selection" operation pertains to the time required for selecting a surface from the alternatives presented by the block faces so that it matches a given mentally recoded stimulus unit (a perceived portion of the stimulus pattern that has been reprocessed into units like those of the various block faces). Experimental manipulations of relevant task parameters have shown that when attempting to find such a match, subjects take longer to select a correctly oriented two-color surface than a correctly oriented solid-color surface (Royer, 1977;Schorr, Bower, & Kiernan, 1982).…”
Section: Daniel B Berch and Mark M Leach University Of Cincinnat~ Cmentioning
confidence: 99%
“…partially responsible for the longer selection times (Schorr et al, 1982). That is, with two-color surfaces, one does not simply have more alternatives from which to choose, one must select the correct orientation of the block face.…”
Section: Daniel B Berch and Mark M Leach University Of Cincinnat~ Cmentioning
confidence: 99%
See 3 more Smart Citations